Ultra-resolution scalable microprinting - Callum Vidler; Kenneth Crozier; David Collins (Microsystems & Nanoengineering, 2023)
Abstract Projection micro stereolithography (PµSL) is a digital light processing (DLP) based printing technique for producing structured microparts. In this approach there is often a tradeoff between the largest object that can be printed and the minimum feature size, with higher resolution generally reducing the overall extent of the structure. The ability to produce structures with high spatial resolution and large overall volume, however, is immensely important for the creation of hierarchical materials, microfluidic devices and bioinspired constructs. In this work, we report a low-cost system with 1 µm optical resolution, representing the highest resolution system yet developed for the creation of micro-structured parts whose overall dimensions are nevertheless on the order of centimeters. To do so, we examine the limits at which PµSL can be applied at scale as a function of energy dosage, resin composition, cure depth and in-plane feature resolution. In doing so we develop a unique exposure composition approach that allows us to greatly improve the resolution of printed features. This ability to construct high-resolution scalable microstructures has the potential to accelerate advances in emerging areas, including 3D metamaterials, tissue engineering and bioinspired constructs.